Racial and Ethnic Differences in a Biochemical Marker of Rheumatoid Arthritis Disease Activity. Issue 3 (8th February 2023) - Baker, Rahaf; Mantilla, Bryanna; Graf, Jonathan; Katz, Patricia P.; Goglin, Sarah; Barton, Jennifer L.; Liew, Jean W.; Wysham, Katherine D.
Abstract : Objective: Racial and ethnic disparities in rheumatoid arthritis (RA) disease activity measures have been documented. We compared racial and ethnic differences in disease activity using multiple composite measures, including an objective measure, the multi‐biochemical disease activity (MBDA) score. Methods: Data are derived from the University of California, San Francisco RA Cohort, a longitudinal observational cohort. Participants with at least one MBDA measure and self‐reported race and ethnicity were included. Multivariable linear regression evaluated the association between race and ethnicity groups and mean MBDA score, adjusting for potential confounders, including symptom duration and medication use. Sensitivity analyses substituted the Clinical Disease Activity Index (CDAI) and the Disease Activity Score‐28 joints with erythrocyte sedimentation rate (DAS28‐ESR) for the MBDA in multivariable models. Results: We included 267 participants (86% female, mean age 52.7 ± 13.3 years). The majority were Latinx (n = 137; 51%), followed by Asian (n = 91; 34%). After adjustment, Latinx participants had the highest mean MBDA score (40.6 ± 2.1) compared with White participants at (32.8 ± 6.7). Black participants had the second highest mean MBDA score, followed by Asian participants (36.3 ± 5.3, 36.0 ± 2.7, respectively), although neither were significantly different from White participants. The trends observed for the CDAI and DAS28‐ESR were similar to those for the MBDA. Conclusion: We found significantly higher disease activity measured by the MBDA and DAS28‐ESR in Latinx participants compared with White participants. We also found significantly higher disease activity in Asian participants compared with White participants with the DAS28‐ESR. Our findings, although limited by the small number of White participants in the referent group, suggest that RA disease activity measures may be influenced by external factors that have differential impacts by racial and ethnic group.